Short‒chain diacyl phosphatidylglycerols: which one to choose for the NMR structural determination of a membrane‒associated peptide from Escherichia coli?. Issue 2 (2004) - Wang Wang, Guangshun Guangshun; Keifer Keifer, Paul A. Paul A.; Peterkofsky Peterkofsky, Alan Alan
Abstract : Diacyl phosphatidylglycerols (PG) are the major anionic lipids in the Escherichia coli membrane. Short‒chain dihexanoyl phosphatidylglycerol (DHPG) was previously utilized for the structural determination, by NMR spectroscopy, of the peptide corresponding to the N-terminal membrane anchor of the glucose‒specific enzyme IIA (IIA Glc ) from E. coli . This study explores the possible use of lipid micelles of dioctanoyl phosphatidylglycerol (DOPG) and didecanoyl phosphatidylglycerol (DDPG) as alternatives to DHPG. At a peptide concentration of 1 mM, the minimum peptide/lipid molar ratios required for the formation of the lipid‒binding amphipathic helix are approximately 1 :40, 1 :5, and 1 :5 for DHPG, DOPG, and DDPG, respectively. Based on the lipid titration, the critical micelle concentration (CMC) of DHPG was estimated to be 50 mM. The 1 H spectral linewidths of the peptide bound to a variety of lipid micelles decrease in the following order: DDPG > DOPG > DHPG. The helical regions of the peptide in different anionic lipids were elucidated based on chemical shift indexes (CSI). Residues Leu2‒Leu9, Leu2‒Val10, and Leu2‒Val10 were found to be helical in DHPG, DOPG, and DDPG, respectively, indicating that the lipid chain length had only a subtle effect on the amphipathic helix of the peptide. In light of the minimum peptide/lipid ratio and the spectral linewidth, and the CSI‒derived peptide structure, DOPG is proposed as a good compromise for structural studies of this membrane‒associated peptide by solution NMR spectroscopy.